2010
DOI: 10.5194/acpd-10-16153-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global fire emissions and the contribution of deforestation, savanna, forest, agricultural, and peat fires (1997–2009)

Abstract: Abstract. New burned area datasets and top-down constraints from atmospheric concentration measurements of pyrogenic gases have decreased the large uncertainty in fire emissions estimates. However, significant gaps remain in our understanding of the contribution of deforestation, savanna, forest, agricultural waste, and peat fires to total global fire emissions. Here we used a revised version of the Carnegie-Ames-Stanford-Approach (CASA) biogeochemical model and improved satellite-derived estimates of area bur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
504
3
16

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(547 citation statements)
references
References 112 publications
3
504
3
16
Order By: Relevance
“…We used GFED4s to investigate the impact of fire emissions. GFED combines satellite information on fire activity and vegetation productivity to estimate burned areas (41) and fire emissions (42). The technique described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…We used GFED4s to investigate the impact of fire emissions. GFED combines satellite information on fire activity and vegetation productivity to estimate burned areas (41) and fire emissions (42). The technique described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the interannual variation in the sources of aerosols over the Maritime Continent by using the Global Fire Emission Database version 3 (van der Werf et al 2010). The correlation coefficient between AOD and organic carbon was 0.94 (see Supplement 1), which indicated that the interannual variation in the sources of aerosols over the Maritime Continent corresponds to that in AOD, which is likely associated with surface conditions partly through the precipitation variations.…”
Section: B Possible Source Of Aod Over the Maritime Continentmentioning
confidence: 99%
“…These represent the amount of the chemical species released per mass of biomass burned and are typically obtained from measurement campaigns in biomass burning regions [11,21,22]. The largest gaseous non-CO 2 fire emissions are those of CO, which are a result of incomplete combustion, especially from smouldering peat fires [12]. Amongst the short-lived constituents emitted from fires, CO has the largest potential to impact atmospheric composition on large geographical scales (hemispheric or even global), due to its comparatively long lifetime of a few months.…”
Section: Gasesmentioning
confidence: 99%
“…The first is to estimate total fuel consumption as the product of the area burned and the fuel consumed per unit area. This approach is used for the series of Global Fire Emissions Database (GFED) products [12], Fire Inventory from NCAR (FINN) [13] and, for particulate emissions, the Fire Locating and Modeling of Burning Emissions inventory (FLAMBE) [14].…”
Section: Effects On Atmospheric Composition Emission Estimatesmentioning
confidence: 99%
See 1 more Smart Citation